504 Using multiplexed immunofluorescence to quantitatively analyze myeloid derived suppressor cells (MDSCs) in relation to tertiary lymphoid structures (TLS) in bladder cancer. (9th November 2020) - Juncker-Jensen, Anna; Huang, Gang; Nagy, Mate; Lu, Xin
Abstract : Background: An intriguing phenomenon in many solid tumors is the de novo lymphoid neogenesis of tertiary lymphoid structure (TLS). However, it remains unclear whether spontaneous TLS restricts or promotes tumor progression. MDSCs are major contributors to tumor evasion of adaptive immune responses. We hypothesize that MDSCs repel TLS as a histological pattern in bladder cancers. Methods: To perform a spatial analysis of MDSDs and other immune cell phenotypes in the bladder tumor microenvironment we used MultiOmyx™, an immunofluorescence (IF) assay utilizing a pair of directly conjugated Cyanine dye-labeled (Cy3, Cy5) antibodies per round of staining. Using a 14-marker panel and proprietary cell segmentation and classification algorithms developed at NeoGenomics we have analyzed the presence of TLS (positive for CD20, CD3, and PNAd), followed by a spatial analysis of MDSCs, T cell subtypes, and M1/M2-type tumor-associated macrophages (TAMs) in relation to the TLS in 25 FFPE samples from patients with bladder cancer. Results: To test our initial hypothesis that MDSCs repel TLS in bladder cancer, we quantitated the presence of immune cell phenotypes inside the TLS, and in tissue regions near and far from the TLS. As expected we found a significantly higher density of B cells and T cells present inside the TLS compared to either near or far from the TLS. However, when quantitating MDSCs we found a linear decrease related to their proximity to the TLS, with a 25% lower density in the region near the TLS, and a 46% decrease in the regions far from the TLS. This pattern was not observed for TAMs that were found at the same density inside, near, or far from the TLS, confirming that this pattern is MDSC specific. We are currently performing further analysis of MDSCs co-expressed with either CXCR2 or iNOS for additional answers to the possible mechanisms behind this finding. Conclusions: The finding on the co-abundance of MDSCs and T/B cells following the distance from TLS suggests that MDSCs may repel TLS-derived T and B cells through cell-cell interaction via physical proximity. This study has important implications for bladder cancer immunotherapy.